2020
DOI: 10.12681/jhvms.25098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Purslane powder and Zinc supplementation on the performance, egg quality, antioxidant system and liver histopathology of lead-exposed laying Quails

Abstract: To determine effects of Purslane (Portulaca oleracea) and zinc supplementation in lead exposed quails, 180 adult female quails allocated into 9 groups. 1. Negative Control (NC, Fed with a corn-soy-based diet), 2. Cornsoy-based diet supplemented with 500 mg/kg lead acetate (Positive control), 3. Positive control supplemented with 0.5 % Purslane powder (PP), 4. Positive control supplemented with 1 % PP, 5. Positive control supplemented with 1.5 % PP, 6. Positive control supplemented with 140 mg/kg zinc, 7. Posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Alagawany et al (2018) found that dietary supplementation with Pb was not affected the egg quality criteria in laying quails. Faryadi et al (2020) demonstrated that dietary Pb supplementation at 500 ppm for 5 weeks had no effect on egg yolk weight, albumin weight, eggshell weight, shape index, and shell thickness in Japanese quails. A significant decrease in shell thickness in the Pb group found in this study (Table 3, P˂0.05) may be due to the suppression of calcium metabolism (Saly et al 2004).…”
Section: Fig 3: the Survivability Rate Of Quails (%)mentioning
confidence: 96%
“…Alagawany et al (2018) found that dietary supplementation with Pb was not affected the egg quality criteria in laying quails. Faryadi et al (2020) demonstrated that dietary Pb supplementation at 500 ppm for 5 weeks had no effect on egg yolk weight, albumin weight, eggshell weight, shape index, and shell thickness in Japanese quails. A significant decrease in shell thickness in the Pb group found in this study (Table 3, P˂0.05) may be due to the suppression of calcium metabolism (Saly et al 2004).…”
Section: Fig 3: the Survivability Rate Of Quails (%)mentioning
confidence: 96%